Thoracic myeloradiculopathy due to multilevel ossification of ligamentum flavum - Yunus Kuntawi Aji; Abdul Hafid Bajamal; Rizki Meizikri; Muhammad Faris (Indoscholar, 2020)
Ossification of ligamentum flavum (OLF) is calcification of the ligamentum flavum, which might narrow the spinal canal and causes myeloradiculopathy. This condition mainly affects the lower thoracal segment. Published reports on OLF are mostly from East Asia. There was only one Indonesian OLF case that had been published. The majority of OLF involves a single level only. This is the first Indonesian case-report on multilevel OLF. Through this case report, we aim to describe the natural history of the patient and our treatment strategy in managing the multilevel OLF case. Delayed time to surgery is the key contributory factor in unfavorable surgical outcome in thoracic OLF. Choosing an appropriate surgical procedure is important. The neurological symptoms of the patient may not improve or worsen when an inadequate surgical procedure is used.